Pengaruh Discount dan Store Atmosphere terhadap Perilaku Impulse Buying (Studi Kasus pada Konsumen Lottemart Wholesale Semarang) - Amsani, Putri Deacitra; Sudharto, Sudharto (Jurnal Ilmu Administrasi Bisnis, 2017)
Retail business in Indonesia is growing so rapidly. That matter, which requires the owners of retail outlets must have marketing strategies to survive in competition fairly tight retail businesses, so the company’s purpose which is increasing profits can be achieved. Retailer profits obtained can be sourced from impulse buying. Impulse buying can be influenced by discount and store atmosphere. Lottemart Wholesale Semarang as a modern retails in Semarang. In 2016, Lottemart Wholesale Semarang’s debit customer has been decreased, which decreased 3,99% or 15.935 customers. The decrease in debit customer discharge causes a decrease in the company's profit so that the planned targets can not be achieved.The purpose of this research is to know the influences between the variable discount and variabel store atmosphere against a impulse buying on customers Lottemart Wholesale Semarang. The type of research is explanatory research and the number of sample taken is 100 respondents. The sampling technique are accidental sampling and purposive sampling. The data analysis technique is a correlation test data analysis, determination test, simple linear regression test, multiple linear regression test, t test and F test using IBM SPSS (Statistical Product and Service Solutions) program version 16.0. Based on the analysis, it is concluded that discount and store atmosphere has an influence on from impulse buying, that has been proved through simple linear regression that result regression value, discount has an influence on impulse buying of 0.624 and store atmosphere has an influence on impulse buying of 0,350. Therefore it can be advised that Lottemart Wholesale Semarang should conduct a survey and monitor competitor prices to be more competitive. In addition, store atmosphere can be improved by manage display product, colors and lighting of the room, and improve air circulation of the room so consumers are more comfortable and happy when shopping in the store.